The Economic Vibrancy of Muslims during Ramadan - Haris, Abdul; Rismawati, Rismawati; Marlina, Marlina; Mustomi, Otom (AMCA Journal of Community Development, 2025)
The month of Ramadan, which is a holy month for Muslims, has a significant impact on the economy in various countries with large Muslim populations. During this month, Muslims observe fasting from sunrise to sunset. These changes in routine and spiritual focus create several distinctive economic trends that recur every year. Several important aspects of economic activity in the month of Ramadan include food and beverage consumption, increased sales of food and clothing, the food service sector, changes in working hours, e-commerce, hospitality and food services, entrepreneurial innovation, etc. All of these aspects greatly influence the economy for the perpetrators. Ramadan brings complex changes in the economy from increased personal consumption to changes in social and commercial activities. Despite challenges such as reduced productivity in some sectors, this month also offers many economic opportunities, especially in retail, food and tourism. The atmosphere of the month of Ramadan seems to be the same because it is present every year, but if you examine it, there are always different phenomena. The unique phenomenon every Ramadan will bring out the creativity of business people. Several places around the world have prepared their routine agendas to welcome the holy month of Ramadan. But there are also those that are surprising. This means that business activities only occur in the month of Ramadan and will close after Ramadan is over. The economic impact on the communities and areas where entrepreneurs trade is that there is quite a large circulation of money and exchange of goods. Therefore, it is very interesting to research in more depth using qualitative methods, in order to obtain in-depth data. In fact, it is alleged that there has been an extraordinary increase as a result of the exchange and circulation of money.